Heart transplantation due to advanced chronic heart failure after complete correction of tetralogy of Fallot - Koželj, Mirta (Zdravniški vestnik, 2013)
A 52-year-old patient decades after complete correction of tetralogy of Fallot is presented. The main late complication was left ventricular failure with consequential congestive heart failure. Heart transplantation was the only therapeutic option.
Keywords: adults; heart; heart transplantation; left ventricular failure; odpoved levega prekata; srce; tetralogija Fallot; tetralogy of Fallot; transplantacija